Cold Compress on Vertebra (Cervical) on The Pain Scale of Postoperative Patients - Dewi Setyawati; Khoiriyah Khoiriyah; Nury Sukraeny (Humanistic Network for Science and Technology (HNST), 2018)
Postoperative pain is the most common problem in hospital. One of the non-pharmacological actions to reduce postoperative pain is cold compresses. A cold compress is one of the distraction techniques that is often used in health services to overcome the problem of postoperative pain. This study aimed to determine the scale of pain before and after cold compress in the vertebrae (cervical) in postoperative patients. Method: This study was a quantitative study with a quasi-experimental method to determine the pain scale of postoperative patients before and after cold compress (cervical). The sample size were 16 postoperative patients in the KRMT Wongsonegoro Hospital, Semarang, Indonesia. The results of this study indicates that the average pain scale of postoperative patients before cold compressions on the vertebrae (cervical) was 5.44. While the pain scale of postoperative patients after cold compress on the vertebrae (cervical) was 3.25. There was difference in the mean pain scale of postoperative patients before and after cold compress on the vertebrae (cervical) with p-value = 0.000. The cold compress effectively reduces postoperative pain because with a cold compress on the cervical cause transmission of pain is closed so the cortex cerebral cannot receive signals because the pain has been blocked with cold stimulation that reaches the brain first. This is related to gate control theory where the stimulation of the skin in the form of cold compress in the cervical area which is located adjacent to the brain and rich in blood vessels, the activation of transmission of larger and faster A-beta sensory nerve fibers, thus closing the